An Investigation on the Effects of Vibrations Applied to the Machining Tank on Geometric Wear of Tool Electrode in Electrical Discharge Machining - Ali ÖZGEDİK; Sadık Mert BALCI; Muhammed Emin ERDİN; Yağmur KOPRAMAN (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
In this study, experiments are conducted with different machining conditions such as vibration frequency, discharge current and pulse duration to investigate the effects of vibrations applied to the machining tank on geometric corner wear of tool electrode and performance outputs in Electrical Discharge Machining. Tool wear rate (TWR) and relative wear (RW) are dropped at experiments with machining tank vibration (MTV-EDM), when compared to experiments without vibrations. According to the results of experiments, vibrations applied to the machining tank have caused a decrease in the values of electrode corner radius.